Two-particle azimuthal correlations in γp interactions using pPb collisions at sNN=8.16TeV - KAYA, MİTHAT (My University, 2023)
The first measurements of the Fourier coefficients (VnΔ) of the azimuthal distributions of charged hadrons emitted from photon-proton (γp) interactions are presented. The data are extracted from 68.8 nb−1 of ultra-peripheral proton-lead (pPb) collisions at sNN=8.16TeV using the CMS detector. The high energy lead ions produce a flux of photons that can interact with the oncoming proton. This γp system provides a set of unique initial conditions with multiplicity lower than in photon-lead collisions but comparable to recent electron-positron and electron-proton data. The VnΔ coefficients are presented in ranges of event multiplicity and transverse momentum (pT) and are compared to corresponding hadronic minimum bias pPb results. For a given multiplicity range, the mean pT of charged particles is smaller in γp than in pPb collisions. For both the γp and pPb samples, V1Δ is negative, V2Δ is positive, and V3Δ consistent with 0. For each multiplicity and pT range, V2Δ is larger for γp events. The γp data are consistent with model predictions that have no collective effects.
Keywords: Fizik; Temel Bilimler; Physics; Natural Sciences; Temel Bilimler (SCI); FİZİK, NÜKLEER; Natural Sciences (SCI); PHYSICS; PHYSICS, NUCLEAR; Nükleer ve Yüksek Enerji Fiziği; Fizik Bilimleri; Nuclear and High Energy Physics; Physical Sciences; CMS; Collectivity; Photon-proton